Corporate Governance: The Linkage to Firm Performance in Malaysia - Aseh, Khairi; Pathmanathan, P. Ravindran (Archives of Business Research, 2020)
This paper focuses on corporate governance applied in Malaysia and how it contributes to the success of the company. Over recent years, with corporate scandals and the global financial crisis, the new idea of corporate governance has attracted rising scrutiny in the business world. It is viewed as a legal obligation that requires the fostering of the integrity of the law and the delivery of ethical advice. Corporate governance is seen as an significant resource for corporate financial efficiency, and investor investment decisions have become a more serious issue, with the result that the relationship between corporate governance mechanisms and financial performance assessment has drawn researchers ' attention in established and emerging cities over the last decade. A total of 215 firms on the KLSE (Kuala Lumpur Stock Exchange) were listed for this report in 2017. Results have demonstrated that corporate governance indicators have a major effect on company efficiency and business value assessment in general. Through analyzing the structure of the group, the ROA and Tobin q calculation variables had a major positive impact. In comparison, the CEO duality was positively associated with all dependent variables, and the number of board committees was found to be negatively correlated with all calculated variables, and strongly correlated with ROA. The challenges of corporate governance are addressed in the final part of the paper.